Origins and Evolution of Human Tandem Duplicated Exon Substitution Events. (8th November 2022) - Martinez-Gomez, Laura; Cerdán-Vélez, Daniel; Abascal, Federico; Tress, Michael L
Abstract: The mutually exclusive splicing of tandem duplicated exons produces protein isoforms that are identical save for a homologous region that allows for the fine tuning of protein function. Tandem duplicated exon substitution events are rare, yet highly important alternative splicing events. Most events are ancient, their isoforms are highly expressed, and they have significantly more pathogenic mutations than other splice events. Here, we analyzed the physicochemical properties and functional roles of the homologous polypeptide regions produced by the 236 tandem duplicated exon substitutions annotated in the human gene set. We find that the most important structural and functional residues in these homologous regions are maintained, and that most changes are conservative rather than drastic. Three quarters of the isoforms produced from tandem duplicated exon substitution events are tissue-specific, particularly in nervous and cardiac tissues, and tandem duplicated exon substitution events are enriched in functional terms related to structures in the brain and skeletal muscle. We find considerable evidence for the convergent evolution of tandem duplicated exon substitution events in vertebrates, arthropods, and nematodes. Twelve human gene families have orthologues with tandem duplicated exon substitution events in both Drosophila melanogaster and Caenorhabditis elegans . Six of these gene families are ion transporters, suggesting that tandem exon duplication in genes that control the flow of ions into the cell has an adaptive benefit. The ancient origins, the strong indications of tissue-specific functions, and the evidence of convergent evolution suggest that these events may have played important roles in the evolution of animal tissues and organs.